Characterization and Apportionment of Sources of Indoor air Particulate Matter of aecd Campus, Dhaka (Journal of Bangladesh Academy of Sciences, 2009)
Ambient particulate matter (PM10 and PM2.5) samples were collected in different laboratories and sitting rooms at the Atomic Energy Centre Dhaka campus in Dhaka on weekdays using AirMetrics Samplers from September to December 2006.  The samples were analyzed for elemental concentrations by ED XRF method.  Black carbon was analyzed by reflectance.  The data sets were analyzed by reconstructive mass (RCM) methods to check the mass closer and also to identify the possible sources of atmospheric aerosols in these closed areas.  It was observed that in these closed areas, 74 to 98% of the particulate mass belong to fine particles mass (PM2.5).  Mostly three and four sources have been identified in both PM10 and PM2.5 fractions respectively.  The sources are soil, combustion products (signature elements are BC and OC), Pb and Zn containing sources.  It was found that about 70 to 98% of total mass is black carbon together with organic carbon.   Keywords:  RCM, PM, AECD campus, XRF method DOI: 10.3329/jbas.v33i1.2947 Journal of Bangladesh Academy of Sciences, Vol. 33, No. 1, 25-36, 2009